Discussion (Scottish Historical and Archaeological Internet Reports, 2009)
The burnt mound is the first to be recorded in Lochaber and is therefore an important contribution to our understanding of the distribution of these features. Aspects of distribution, morphology and function of burnt mounds is considered.